Colloidal Silica Rods: Material Properties and Fluorescent Labeling. (11th February 2014) - Kuijk, Anke; Imhof, Arnout; Verkuijlen, Margriet H. W.; Besseling, Thijs H.; van Eck, Ernst R. H.; van Blaaderen, Alfons
<x xml:space="preserve">Abstract</x> In this paper, the characterization and fluorescent labeling of silica rods are reported. These rods are synthesized following a recently reported method. Material properties of the silica rods measured with NMR, elemental analysis, TGA, and porosimetry are compared with those of well‐established Stöber silica spheres. Additionally, silica rods are made suitable for quantitative real‐space studies by confocal microscopy. Several methods of fluorescent labeling to prepare rods with different fluorescent patterning, ranging from uniform fluorescence levels to gradients from one rod‐end to the other, and even patterns of several colors are presented and discussed.